Prescription rates of common medications in patients with decompensated cirrhosis in Germany - Labenz, Christian; Kostev, Karel; Galle, Peter Robert; Wörns, Marcus-Alexander; Schattenberg, Jörn M. (Zeitschrift für Gastroenterologie, 2021)
Background Adequate pharmacological treatment is of pivotal importance to improve prognosis in patients with decompensated liver cirrhosis. We studied the adherence to recommended pharmacological treatments as secondary prevention in cirrhotic patients following a first decompensation in German primary care.Methods Using the Disease Analyzer Database, the current study sample included patients with liver cirrhosis who had an initial diagnosis of a first decompensation event between 2015 and 2018 (index date) and a follow-up time of at least 6 months after the index date. Pharmacological treatments following the 6 months after the index date were studied.Results The study included 1538 patients with a first decompensation event. The frequency of first-time complications of cirrhosis was 60% new onset of ascites, 25% overt hepatic encephalopathy (HE), 3% spontaneous bacterial peritonitis (SBP), and 12% acute variceal bleeding. The adherence to guideline-recommended treatment following the initial decompensation was highest for ascites, with 91.3% of patients receiving diuretics. Non-selective beta-blockers following an event of variceal bleeding were prescribed in 69.1% and lactulose and/or rifaximin in 59.1% after a bout of HE. The frequency of prescriptions of antibiotics after SBP was 60.4%. Potenzially harmful prescribed medications included non-steroidal anti-inflammatory drugs in 15.5%, benzodiazepines in 12.8%, opioids in 9.5%, and proton pump inhibitors in 73.7%.Conclusion Our findings underline the need for intensified efforts to distribute practice guidelines for liver cirrhosis and increase awareness of over-prescribing of potentially harmful medication.
Keywords: Gastroenterologie; Hepatologie; Pharmakologie; Grundversorgung; Qualität der Pflege